Congenital malformations in the neonatal unit of Arifin Achmad Hospital, Pekanbaru: occurrence and trends - Dewi Anggraini Wisnumurti (Indonesian Pediatric Society, 2012)
Background Congenital malformations are a global and continualissue, contributing to neonatal mortality. The incidence andprevalence, as well as distribution of congenital malformationsvary among countries.Objective To determine the 'prevalence, distribution, and trendsin congenital malformations which are important to develop plansto cope Mth the problem.Methods We reviewed all cases of congenital malformationsadmitted to the Neonatal Unit, Department of Child Health,Arifin Ahmad Hospital from 2008 to 2010. Data were collectedfrom medical records. Diagnoses of congenital malformationswere established by history-taking, physical examination,and specific laboratory tests. Trends in the distribution ofcongenital malformation types, as well as clinical outcomes werehighlighted.Results During the study period there were 2,317 infants admit-ted to the Neonatal Unit, 724 in 2008, 772 in 2009, and 821 in2010. Most patients were referred by other hospitals, at the ageof 0-3 days. Most patients had normal birth weight and were de-livered vaginally. Of the 2,317 infants, 302 were diagnosed withcongenital malformations; the most common congenital malfor-mations were of the digestive tract. The distribution of anomalytypes was relatively constant over time, but the proportion ofpatients Mth congenital malformations discharged alive increasedin the latter two years of the 3-year period studied.Conclusion Most infants in our study had congenital malforma-tions involving the gastrointestinal tract. Distribution trendswere constant over time. Further efforts should be made to bettermanage future cases. [Paediatr lndones. 2012;52:284,8].